Shoulder 3D range of motion and humerus rotation in two volleyball spike techniques: injury prevention and performance - Seminati. E.; Marzari, A.; Vacondio, O.; Mnetti, A. E. (Sports Biomechanics, 2015)
Repetitive stresses and movements on the shoulder in the volleyball spike expose this joint to overuse injuries, bringing athletes to a career threatening injury. Assuming that specific spike techniques play an important role in injury risk, we compared the kinematic of the traditional (TT) and the alternative (AT) techniques in 21 elite athletes, evaluating their safety with respect to performance. Glenohumeral joint was set as the centre of an imaginary sphere, intersected by the distal end of the humerus at different angles. Shoulder range of motion and angular velocities were calculated and compared to the joint limits. Ball speed and jump height were also assessed. Results indicated the trajectory of the humerus to be different for the TT, with maximal flexion of the shoulder reduced by 10 degrees, and horizontal abduction 15 degrees higher. No difference was found for external rotation angles, while axial rotation velocities were significantly higher in AT, with a 5% higher ball speed. Results suggest AT as a potential preventive solution to shoulder chronic pathologies, reducing shoulder flexion during spiking. The proposed method allows visualisation of risks associated with different overhead manoeuvres, by depicting humerus angles and velocities with respect to joint limits in the same 3D space.